DIVERSITY OF SEED EEL AND ADULT EEL (Anguilla sp.) IN DUMOGA RIVER, NORTH SULAWESI - Ni Putu Dian Kusuma; Endang Yuli Herawati; Abu Bakar Sambah (Universitas Mataram, 2021)
The spawning sites of Anguilla borneensis and Anguilla celebesensis were in the seas off Sulawesi and the Gulf of Tomini, the spawning sites of Anguilla marmorata and Anguilla bicolor pacifica were in the western part of the North Pacific. The purpose of this study was to find out information on the diversity of eel seeds and adult eels in the Dumoga River based on the abundance of eel seeds and gonad maturity of adult eels. The eel species consisted of 1,106 A. marmorata, A. bic. pacifica as many as 854 tails and Anguilla spp as many as 291 individuals. The caught eel fish were separated based on the morphology of the eel species. Segregation of catches based on special characteristics of eel, namely preanal and predorsal lengths. Anodorsal values were divided into three groups, namely ±15.57% (A. marmorata); ±1.18% (A. bicolor pacifica) and ±7.09% (Anguilla spp.). Meristic values of A. marmorata for spine (TB) total 104-106 units, pre-dorsal TB 17-19, pre-anal TB 36-39 and ano-dorsal TB 18-20. Meristic values of A. bicolor pacifica for spine (TB) totaled 108-112, pre-dorsal TB 32-36, pre-anal TB 32-39 and ano-dorsal TB 0-3. Meristic values of Anguilla spp for spinal (TB) totaled 100-106, pre-dorsal TB 27-29, pre-anal TB 30-33 and ano-dorsal TB 6-12. The growth pattern of adult eels is negative allometric, i.e. the body length gains faster than the slower body weight gain. The condition of adult eels in the Dumoga River is not fat because the condition factor ranges from 0.0024-0.0036. The average length of adult eels was 58.92cm in Anguilla marmorata (GIC 1.57–2.90%); 54.2cm in A. bicolor pacifica (ICI 1.27–2.79%) and 52.32cm in Anguilla spp (ICI 0.97-2.50%).